Acute oxidative effect and muscle damage after a maximum 4 min test in high performance athletes - Ribeiro Ferreira, H.; Gill Ferreira, P.; Loures, J. P.; Fernandes Filho, J.; Fernandes, L. C.; Sousa Buck, H.; Montor, W. R. (PLOS ONE, 2016)
The purpose of this investigation was to determine lipid peroxidation markers, physiological stress and muscle damage in elite kayakers in response to a maximum 4-min kayak ergometer test (KE test), and possible correlations with individual 1000m kayaking performances. The sample consisted of twenty-three adult male and nine adult female elite kayakers, with more than three years` experience in international events, who voluntarily took part in this study. The subjects performed a 10-min warm-up, followed by a 2-min passive interval, before starting the test itself, which consisted of a maximum 4-min work paddling on an ergometer; right after the end of the test, an 8 ml blood sample was collected for analysis. 72 hours after the test, all athletes took part in an official race, when then it was possible to check their performance in the on site K1 1000m test (P1000m). The results showed that all lipoproteins and hematological parameters tested presented a significant difference (p=0.05) after exercise for both genders. In addition, parameters related to muscle damage such as lactate dehydrogenase (LDH) and creatine kinase (CK) presented significant differences after stress. Uric acid presented an inverse correlation with the performance (r = -0.76), while CK presented a positive correlation (r = 0.46) with it. Based on these results, it was possible to verify muscle damage and the level of oxidative stress caused by indoor training with specific ergometers for speed kayaking, highlighting the importance of analyzing and getting to know the physiological responses to this type of training, in order to provide information to coaches and optimize athletic performance.